A Net of Little Stories, Feministic Hunt in the Post-biological Landscape. Towards Donna Haraway, ModestWitness@Second_Millenium.FemaleMan_Meets_OncoMouse: Мрежа од малечки приказни, феминистички лов во постбиолошкиот пејзаж. Кон Donna Haraway, ModestWitness@Second_Millenium.FemaleMan_Meets_OncoMouse - Shikov, Viktor; Tasev, Saše (Identities: Journal for Politics, Gender and Culture, 2001)
Author(s): Victor Shikov | Виктор Шиков Title (English): A Net of Little Stories, Feministic Hunt in the Post-biological Landscape. Towards Donna Haraway, ModestWitness@Second_Millenium.FemaleMan_Meets_OncoMouse Title (Macedonian): Мрежа од малечки приказни, феминистички лов во постбиолошкиот пејзаж. Кон Donna Haraway, ModestWitness@Second_Millenium.FemaleMan_Meets_OncoMouse Translated by (English to Macedonian): Saše Tasev | Саше Тасев Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 1, No. 1 (Summer 2001) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 229-231 Page Count: 3 Citation (English): Victor Shikov, “A Net of Little Stories, Feministic Hunt in the Post-biological Landscape. Towards Donna Haraway, ModestWitness@Second_Millenium.FemaleMan_Meets_OncoMouse,” Identities: Journal for Politics, Gender and Culture, Vol. 1, No. 1 (Summer 2001): 229-231. Citation (Macedonian): Виктор Шиков, „Мрежа од малечки приказни, феминистички лов во постбиолошкиот пејзаж. Кон Donna Haraway, ModestWitness@Second_Millenium.FemaleMan_Meets_OncoMouse,“ превод од англиски Саше Тасев, Идентитети: списание за политика, род и култура, т. 1, бр. 1 (лето 2001): 229-231.